A RETROSPECTIVE REVIEW OF THE DEVELOPMENT OF PHYSICAL TRAINING MODELS FOR THE SECURITY AND DEFENSE SECTOR SPECIALISTS - Hnydiuk, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article establishes that the main factor determining the emergence and justification of new models of physical training is a change in the nature and methods of combat operations. It has been established that in professional armies, as a rule, the "conditioned" model of physical training is implemented, in mixed type armies – the "sports" model, and in conscription armies the "military-applied" and "gymnastic" models are realized. At the current stage of development and functioning of the components of the security and defense sector there exist "conditional" (specially developed for professional armies) and "sports" models (for military formations and law enforcement bodies, staffed according to the principle of mixed staffing – contract servicemen and conscripts). The conditional model of physical training is a practical embodiment of the concept of "total physical readiness", developed in the United States under the influence of insights into the nature of modern warfare and the characteristics of combat operations. This concept, in various modifications, has been adopted by other NATO members. The concept was formed during the modernization of combat and physical training in connection with the transition to the professional method of manning the U.S. armed forces. This concept is based on the experience of past wars, ideas about the characteristic features of modern warfare and the consequent requirements for the physical training of troops, as well as the achievements of science and practice in the field of physical culture and sports. A close correlation between physical and mental readiness of servicemen has been established.The psychological orientation of physical training involves the development of moral and volitional qualities of military personnel in order to increase resistance to the effects of combat stress. The concept of mobilization was developed mainly for armies with a mixed method of manning. The use of a sports model of physical training provides the greatest motivation for military personnel to engage in physical exercises and achieve high results, as well as helping to level out differences between different categories of personnel.
Keywords: physical training model, physical training concept, specialists in the security and defense sector, professional training, physical preparedness